2014
DOI: 10.1080/14689367.2014.902037
|View full text |Cite
|
Sign up to set email alerts
|

Shadowing for actions of some finitely generated groups

Abstract: We introduce a notion of shadowing property for actions of finitely generated groups and study its basic properties. We formulate and prove a shadowing lemma for actions of nilpotent groups. We construct an example of a faithful linear action of a solvable Baumslag-Solitar group and show that the shadowing property depends on quantitative characteristics of hyperbolicity. Finally we show that any linear action of a non-abelian free group does not have the shadowing property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Since T g is expansive and g ∈ K, T K is expansive. As K is a normal subgroup of G by Proposition 2(N1) in [7], applying Lemma 3.5, we get the result.…”
Section: To Show That H Is Upper Semicontinuous Fix X ∈ Dom(h) and Amentioning
confidence: 68%
See 3 more Smart Citations
“…Since T g is expansive and g ∈ K, T K is expansive. As K is a normal subgroup of G by Proposition 2(N1) in [7], applying Lemma 3.5, we get the result.…”
Section: To Show That H Is Upper Semicontinuous Fix X ∈ Dom(h) and Amentioning
confidence: 68%
“…Let n > 1 and assume that this lemma holds for each nilpotent group with nilpotent degree less than or equal to n − 1. Put G 1 = [G, G] and K =< G 1 , g >, then K has the nilpotent degree at most n − 1 by Proposition 2(N2) in [7]. It is known that G 1 is finitely generated by Lemma 6.8.4 in [5] and hence K is finitely generated.…”
Section: To Show That H Is Upper Semicontinuous Fix X ∈ Dom(h) and Amentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in 2014, Osipov and Tikhomirov [12], introduced the notion of shadowing property for finitely generated group actions. Barzanouni in [3] used the notion of shadowing property to study chain recurrent sets whereas Chung and Lee in [5] showed that expansive action which has shadowing property are always topologically stable.…”
Section: Introductionmentioning
confidence: 99%